Teaching Research Method Using a Student-Centred Approach? Critical Reflections on Practice - Barraket, J. (Journal of University Teaching and Learning Practice, 2005)
This article presents a reflective case study analysis of anattempt to enhance student learning through theintroduction of student-centred teaching methods in amasters-level social research methods subject. Theintroduction of a range of specific techniques, includingcase study teaching, problem based learning, groupwork,role-play and simulation, is reflected upon. The articleconcludes that the re-orientation of the curriculum towardstudent-centredness in this case had a positive effect onstudent performance, learning experience and subjectevaluation. In particular, the use of student-centredtechniques facilitated a strong social context for learning,and provided students with a common experientialframework from which to explore the technical aspects ofthe curriculum. However, the analysis also found thatstudents continued to place value on more formalteaching methods, and that the value of student-centredtechniques in this case rested in the way in which theywere integrated with more didactic teaching practice.